**Question:**logarithms

for the first part:

to find g of f(x), just substitute the whole expression of f(x) in place of x in g(x), thus giving you - 2x^2+6x-1

for the second part, I'm assuming you mean find log 3 base 7:

in which case, the answer is given by (log 3 base 10)/(log 7 base 10).

the rule here is log a base b = (log a base c)/(log b base c), where c can be any base you are comfortable with

im lost

1) if you mean...

g(f(x)) = 2(x^2 + 3x) - 1 = 2x^2 + 6x - 1 or

f(g(x)) = (2x - 1)^2 + 3(2x - 1) = 4x^2 - 4x + 1 + 6x - 3 =

4x^2 + 2x - 2

2) 3^b = 7 so just solve for b.

- Web site help please?
- 2.54 centigrams = how many decigrams?
- Find the equation of the straight line containing the point (3,2)&making positive equal intercepts on axes.?
- Write pqqqqrr in exponential form?
- Need ideas for a precalculus final project, "artistic expression"?
- A maths problem..?
- HElpppp again?
- I SERIOUSLY NEED HELP PLEASE GO TO MY PREVIOUS QUESTION ON MATH PROBLEMS AND SOLVE i will give u best answer?
- Any suggestions for a "How To" project?
- What was the...?